Differentiated Learning Using ESS-MATH-Based PBL Model on Problem-Solving Ability Reviewed from Learning Style - Ardiyanto, Bagas; Firmansah, Fery; Tasari, Tasari (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2025)
The development of the era of globalization is accelerating, which must be supported by the ability of expert students. This study aims to find out how content-differentiated learning through the ESS-MATH-based Problem-Based Learning model affects the ability of class X students of SMK N 1 Klaten to solve problems from a learning style. This study uses a descriptive approach with qualitative research methods. The instruments used were David Kolb's learning style questionnaire, the ESS-MATH application and problem-solving ability questions. The results obtained are that the application of content-differentiated learning using the ESS-MATH-based PBL model is able to improve students' skills in problem-solving according to their learning style. The ESS-MATH application is a new alternative in the implementation of content-differentiated learning because it can meet the learning needs of students and ease of use.